The problematics of gramatical gender of nouns in romanian grammars - Elena Mădălina STAN SĂVULESCU (Diversitate si Identitate Culturala in Europa)
In Romanian descriptive grammars, noun inflection is a controversial chapter. However, grammarians agree that the noun has the known grammatical categories: gender, number and case, and that gender is not a criterion for inflection, since it is an intrinsic feature of the noun. This paper presents an exploration of the gender subcategories of the noun, as illustrated in the three modern Romanian grammars, and describes both the motivated or unmotivated classification of nouns into the gender subcategories - masculine, feminine and neuter, as well as the general morphological, syntactic and semantic expression of this grammatical category. Thus, an undeniable feature of the gender of the noun is its fixed character because each noun has a gender feature, by which it falls into one of the three subcategories, each of them having its own inflection, characterized by homonyms and specific combinations of desinences. Moreover, there are also nouns whose inclusion in a particular gender subcategory is closely related to the expression of semantic distinctions imposed by natural gender.